PRODUCTION OF CONFECTIONERIES: OPPORTUNITIES FOR IMPLEMENTING NEW TECHNOLOGIES - Emelyanovna Tkeshelashvili, Manana; Alexandrovna Bobozhonova, Galina; Petrovich Gaidukov, Igor (Revista Inclusiones, 2019)
The current trends forming a healthy diet dictate the need to create food products, including confectioneries, with high nutritional value. The use of nontraditional types of raw materials in food production can contribute to their enrichment with proteins and micronutrients. The secondary resources of vegetable raw materials are currently actively used in solving food problems, being an additional source of natural substances. A significant amount of secondary resources is generated during the processing of sunflower seeds. The data on the amino acid composition of high-protein flour from sunflower shrot have been presented in the article. The effect of various dosages of highprotein flour from sunflower shrot on the change in consumer and technological properties of chocolate masses has been explored. The expediency of using this additive in the manufacture of confectioneries, in particular chocolate, has been demonstrated.